(untitled) (Al-Farooq Journal of Sciences, 2026)
Environmental awareness has become an essential factor in promoting sustainable behaviors related to natural resource conservation, particularly water resources. Universities and higher education institutions play a critical role in developing environmental knowledge and responsible behaviors among postgraduate students, who are expected to contribute to future scientific research and decision-making processes. This study aims to investigate the relationship between environmental awareness and sustainable water behavior among postgraduate students. The study adopted a descriptive-analytical approach using an electronic questionnaire distributed to a sample of 102 participants. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS). The results revealed a high level of environmental awareness among the participants, with 79.4% expressing a strong belief in the importance of conserving water resources for future generations, while 69.6% confirmed that environmental awareness contributes to solving water-related problems. The findings also showed that the majority of participants practice positive water conservation behaviors, such as turning off water taps when not needed 73.5% and reporting water leakages 55.9%. The study concluded that there is a positive relationship between the level of environmental awareness and behaviors related to the conservation of water resources. This highlights the importance of strengthening environmental awareness programs and community initiatives to support water sustainability.